PENGARUH KEBERADAAN WISATAWAN ASING TERHADAP PERKEMBANGAN BISNIS PARIWISATA MASYARAKAT DI TUKTUK SIADONG - Grace Berlian Sinambela (Jurnal Ilmiah Administrasita', 2019)
Tuktuk Siadong has become a recreational area since 1960. Tuktuk as one ofthe most famous tourism destination in North Sumatra makes Tuktuk not only visitedby local tourist, but also foreigner. In Tuktuk, most of people use Batak as their mainlanguage, and English or other foreign language as their secondary languages, butonly a few of them can speak Indonesia well. Indirectly, we can say that the localcondition is still maintained, but nationality is abandoned. It is good to keepingtraditionality, as Dove said, it’s a supporting factor of development. But we shouldremember that national language however should be mastered. This research also findthat most of local people start changing their couple preference, preferring foreignerto their fellow local. It caused beside their thought that people who marry foreignerhaving a higher social status, also by their desire to evolve their business, asset andsome.